Songs, stories, dance ...for children [Bladmuziek]. - Chinese People's National Committee for the Defense of Children (Peking : Chinese People's National Committee for the Defense of Children, 1959)
Deze brochure bevat volgende liederen
The Football Match (gedicht)
Little Ping Buys a Book
Train Song
Sunflower Song
King Scatterbrain
Flower Game
Pretty Morning Glory
The Children's Theatre (gedicht
Riddle-me-ree
Flower-staff Dance
¨Paper-cuts
Ways with Date Paste
A Chinese Jacket
Supplement bij Children of China, augustus 1959.
Engels
Bladmuziek
Keywords: kinderen; liederen; jeugdliteratuur; China